On the Boundaries: Professional Photojournalists Navigating Identity in an Age of Technological Democratization. Issue 3 (15th March 2020) - Ferrucci, Patrick; Taylor, Ross; Alaimo, Kathleen I.
ABSRACT: In the wake of fewer and fewer professionals populating photojournalism, this study utilizes in-depth interviews with 21 professional photojournalists to better understand how they construct their identity. With a framework of social identity theory, this research found photojournalists consider clear role conception, adherence to normative journalism ethics and organizational backing as key components of their in-group. They consider professionalism as service, a lack of professional processes, and advocacy key parts of the out-group. These results are then interpreted for their effects on professionalism.